2023
DOI: 10.1002/gj.4759
|View full text |Cite
|
Sign up to set email alerts
|

Identifying moisture transport pathways for north‐west India

Abstract: The isotopic composition (δ18O and δ2H) of precipitation is widely used as a moisture source tracer. In north‐west India, the δ18O, δ2H and D‐excess values of precipitation correlate mainly with air temperature; however, the moisture sources of water vapour are unclear. Therefore, we collected daily precipitation isotope data (n = 425) from 13 rain gauge stations in northwest India in 2013. We established a regional meteoric water line (MWL) for northwest India and local MWLs for all 13 rain gauge stations sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, several studies (Krishnan et al 2016, Guhathakurta et al 2017, Joshi et al 2023b have pointed out that the local surface warming of the Indian subcontinent and the rise in humidity levels have a direct role in increased extreme rainfall events. Roxy et al (2017) revealed a threefold increase in widespread extreme rainfall across the Central Indian regions primarily because of the significant contribution of moisture transport from the Arabian Sea since the 1950s.…”
Section: Physical Connections Between Pre-and Post-1960 Monsoon Rainfallmentioning
confidence: 99%
“…Furthermore, several studies (Krishnan et al 2016, Guhathakurta et al 2017, Joshi et al 2023b have pointed out that the local surface warming of the Indian subcontinent and the rise in humidity levels have a direct role in increased extreme rainfall events. Roxy et al (2017) revealed a threefold increase in widespread extreme rainfall across the Central Indian regions primarily because of the significant contribution of moisture transport from the Arabian Sea since the 1950s.…”
Section: Physical Connections Between Pre-and Post-1960 Monsoon Rainfallmentioning
confidence: 99%
“…We evaluate the causal interference between these hydro-climatic variables using the MCI approach with a maximum 2-day lag period (τmax = 2) and a limit for significance set to 0.05 (α = 0.05), in order to examine the spatially interdependence relationships among each of these variables during 2-day event periods. (Joshi et al, 2023). Over the past decade, researchers have used the HYSPLIT model to identify moisture sources (Wang et al, 2017;Joshi et al, 2023).…”
Section: Causal Discovery Among Hydro-climatic Variablesmentioning
confidence: 99%
“…(Joshi et al, 2023). Over the past decade, researchers have used the HYSPLIT model to identify moisture sources (Wang et al, 2017;Joshi et al, 2023). To determine the backward trajectory following an anomalous precipitation event, this study used the HYSPLIT model.…”
Section: Causal Discovery Among Hydro-climatic Variablesmentioning
confidence: 99%
“…A few studies have attributed the high D-excess to local recycling, in other words, evaporation from the subcontinent itself (Jeelani et al, 2018;Oza et al, 2022;Joshi et al, 2023). Local moisture recycling as the dominant source is unlikely given the volume required to feed the snowpacks and glaciers and support agriculture, and the frequency with which heavy precipitation events occur during the winter months.…”
mentioning
confidence: 99%